2009
DOI: 10.2355/isijinternational.49.1678
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for CeS Formation During Manufacturing of Ce–S–Al Based Grain Refiners for Steels

Abstract: In the present investigation the phase relations within the Ce-S-Al system have been clarified, using a combination of optical microscopy and WDS microprobe analyses. As a starting point high-purity charge materials of cerium, aluminium and Ce 2 S 3 were melted and superheated to about 2 000°C within small tantalum crucibles inside a dedicated laboratory furnace filled with cleaned argon. The main constituent phases detected in the as-solidified samples are CeS, Ce 3 Al, CeAl and g-Ce, where the CeS phase cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This type of CeS dispersed alloy has also been produced with a matrix of Ce-aluminides. [79,80] It is reported that an alloy containing fine dispersion of CeS in a metallic matrix was easily dissolved in the liquid steel but had little effect on the composition of steel. [81] 3.1.4.…”
Section: Rare Earth Metalsmentioning
confidence: 99%
“…This type of CeS dispersed alloy has also been produced with a matrix of Ce-aluminides. [79,80] It is reported that an alloy containing fine dispersion of CeS in a metallic matrix was easily dissolved in the liquid steel but had little effect on the composition of steel. [81] 3.1.4.…”
Section: Rare Earth Metalsmentioning
confidence: 99%